Determinants of Psychological Wellbeing in Lepers - Ningsih, Siska Kusuma; Pradanie, Laily Hidayati, Retnayu (International Journal of Psychosocial Rehabilitation, 2020)
Leprosy cause physical and social disability which can af ect psychological wellbeing. The aim of this study is to analyse factors related to psychological wellbeing in lepers (people with leprosy) at Public Health Center in Surabaya. This study used descriptive correlational design with a cross-sectional research. The population study was lepers in Public Health Center in Surabaya, East Java. The number of samples obtained were 60 lepers by purposive sampling through total population sampling. The dependent variable is psychological wellbeing of lepers and independent variables form of age, sex, education, length of diagnosis, duration of treatment, social support and family support. Data were collected using the Psychological Well Being, social support and family support questionnaires. Statistical tests using Spearman Rho and chi-square were significant <0.05. Psychological wellbeing had a significant relationship with age (p=0.024), sex (p= 0.000), education (p= 0.007), the time of initial treatment (p= 0.033), duration of treatment (p = 0.028), social support (p= 0.000) and family support (p = 0.003). Of all the factors studied, it appears that social support factor shows the strongest relationship with the psychological wellbeing of lepers. In contrast, the time of initial treatment factor has the weakest relationship with the psychological wellbeing of lepers. Further research can be developed by identifying other possible variables and constructing a model of leprosy treatment that can improve psychological wellbeing in people with leprosy.